Implications and Usefulness of Fundamental and Technical Analysis in Stock Market Decision Making - Nagendra, S.; Kumar, Satish; Jayashree, (Indian Journal of Finance, 2018)
This paper threw light on the practical usefulness of fundamental and technical analysis. Company level fundamental analysis may involve examination of financial data, management, business concepts, and competition. Technical analysis is about analyzing past price action and from that deriving a predictive model for the future. Fundamental analysis is more useful for long term trades and investments ; whereas, technical analysis is more useful from a short term perspective. For the purpose of data analysis and interpretation, five market capitalization services companies were selected. These are TCS, Reliance, Coal India, HUL, and Hindustan Zinc. Data for 10 years were collected for these companies. Stock market prices of 10 years of these companies were employed for the technical analysis. Also, balance sheets of 10 years of these companies were employed for fundamental analysis. In the study, it was found that both the analysis were useful in dealing with stock market activities.